Combination Benson's Relaxation Technique and Energy Manajement to Overcome Activity Intolerance Nursing Problems in Coronary Artery Disease Patients: A Case Report - Umy Riskyani; Nita Fitria; Nursiswati Nursiswati (Padjadjaran Acute Care Nursing Journal, 2022)
In patients with Coronary Artery Disease (CAD), activity intolerance is a major issue. Energy management is a non-pharmacological intervention that is commonly used in patients with activity intolerance. The problem of activity intolerance can be overcome with complementary or alternative relaxation therapy, namely the Benson relaxation technique. The goal of this case study is to describe how a combination of Benson relaxation techniques and energy management helped CAD patients with activity intolerance nursing problems. The method used in this study is a case report. Data collection techniques include observation, interviews, physical examinations, and hospital medical records. Interventions are carried out to address the main problem of activity intolerance. In this study, the Benson relaxation technique was given together with energy management, namely, gradual physical activity for 3 days for 20 minutes per day. The results of this case study show that after the Benson relaxation technique intervention, which was given in conjunction with the energy management intervention, these outcomes improved, namely subjective data, complaints of fatigue after decreased activity, and objective data showing improved pulse rate and ease of doing daily activities. In conclusion, the Benson relaxation technique can be applied as a complementary and alternative intervention that is given together with energy management interventions to address the problem of activity intolerance in CAD patients.